Identification and Characterization of the Bioactive Polyphenols and Volatile Compounds in Sea Buckthorn Leaves Tea Together With Antioxidant and α-Glucosidase Inhibitory Activities - Wang, Ningning; Wen, Xiufeng; Gao, Yan; Lu, Shunguang; Li, Yimeng; Shi, Yanbin; Yang, Zhigang (Frontiers in Nutrition, 2022)
Seabuckthorn leaves have been used for tea making in food field gradually. The present study was carried out to characterize the the bioactive polyphenols and volatile compounds in seabuckthorn leaves (SL), seabuckthorn leaves green tea (SGT) and seabuckthorn leaves black tea (SBT) by using high-performance liquid chromatography with an ultraviolet detector (HPLC-UV), the liquid chromatography-mass spectrometry (LC-MS) and headspace solid phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS), in combination with multivariate analysis. A total of 48 non-volatile metabolites and 295 volatile metabolites were identified. Then the total polyphenol and total flavonoid contents in SL, SGT and SBT were also analyzed. Moreover, SL and SGT showed greater antioxidant activities based on DPPH, ABTS and ORAC results. At the concentration of 0.1 mg/mL, their DPPH and ABTS radical scavenging ratios were 66% to 95%, while SBT exhibited lower antioxidant activity of 26% to 44%. SL, SGT and SBT displayed moderate α-glucosidase inhibitory. Keywords: Polyphenols; Volatile compounds; Seabuckthorn leaves tea; LC-MS; HS-SPME-GC-MS; Antioxidant activity; α-glucosidase inhibitory activity.